PERANAN PEMBIASAAN IBADAH DALAM PENGEMBANGAN KARAKTER RELIGIUS SISWA DI SD MUHAMMADIYAH 1 KUDUS - Muhammad Rijal Aufa; Lintang Kironoratri; Much Arsyad Fardani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The influence of the era and technology on children's character formation, along with the significance of character education in cultivating responsibility, honesty, and empathy, is paramount. Ritual habits, such as the Duha and congregational Zuhr prayers, hold substantial spiritual and health benefits in shaping the religious character of students at SD Muhammadiyah 1 Kudus. The research employs a qualitative narrative approach with observation and interviews as data collection techniques. Results reveal the positive impact of habitual religious practices on students' understanding, discipline, and empathy, supported by the school environment and guidance from educators. Nonetheless, hindering factors encompass academic pressure and external environmental influences. Recommendations encompass reinforcing the school's role, collaborating with parents, and integrating ritual habits with innovative teaching methods. This research is anticipated to contribute to religious character education within school settings.